2020
DOI: 10.21608/ejhm.2020.131253
|View full text |Cite
|
Sign up to set email alerts
|

Histopathological and Ultrastructural Alterations in The Renal Cortex of Albino Mice Foetuses Induced by Beta-Lactam Antibiotic 'Amoxicillin'

Abstract: Background: The aim of this investigation was to evaluate the effect of a low and high doses (205 & 820mg/kg body weight, respectively) of the beta-lactam antibiotic amoxicillin on the kidney of maternally treated mice foetuses. Material and Methods: Pregnant mice were allocated into three groups; the first group served as control (injected with the drug solvent) and those of the other two groups were injected intraperitoneally with two doses (205 & 820 mg/kg body weight) of amoxicillin for 8 days from day 7 t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 21 publications
(5 reference statements)
0
1
0
Order By: Relevance
“…In our latest microscopic examination, we observed increased Bowman's space, congestion, necrosis of renal tubular epithelial cell, nuclear hypertrophy, necrosis of renal tubules, degeneration of renal tubule, degenerative changes in kidney glomerulus, widening of the urinary space, hemorrhage b/w tubule, and cell infiltration with pyknotic nuclei in the kidney of amoxicillin-treated rabbits, while previous studies reported that the renal cortex of maternally treated foetus showed erosion of the parietal cells of Bowman's capsule, hypoplasia of the mesangial cells of the glomerulus, and erosion of the epithelial cells lining the proximal and distal convoluted tubules. In the electron microscope level, the renal cortex of foetus maternally treated with amoxicillin showed fusion of the foot processes of the podocytes, partial destruction of the apical brush borders microvilli of the proximal convoluted tubule cells, degeneration of some mitochondria, and fragmentation of the rough endoplasmic reticulum elements [ 20 ] ( Table 7 ). In recent microscopy, we observed necrosis of cardiac cells, cytoplasmic vacuolization, congestion, neutrophilic myocarditis, myofibrillolysis, and pyknotic nuclei in amoxicillin-treated rabbits, while in a previous study, no authentic and related research data are available on heart pathology in connection to our study ( Table 7 ).…”
Section: Discussionmentioning
confidence: 99%
“…In our latest microscopic examination, we observed increased Bowman's space, congestion, necrosis of renal tubular epithelial cell, nuclear hypertrophy, necrosis of renal tubules, degeneration of renal tubule, degenerative changes in kidney glomerulus, widening of the urinary space, hemorrhage b/w tubule, and cell infiltration with pyknotic nuclei in the kidney of amoxicillin-treated rabbits, while previous studies reported that the renal cortex of maternally treated foetus showed erosion of the parietal cells of Bowman's capsule, hypoplasia of the mesangial cells of the glomerulus, and erosion of the epithelial cells lining the proximal and distal convoluted tubules. In the electron microscope level, the renal cortex of foetus maternally treated with amoxicillin showed fusion of the foot processes of the podocytes, partial destruction of the apical brush borders microvilli of the proximal convoluted tubule cells, degeneration of some mitochondria, and fragmentation of the rough endoplasmic reticulum elements [ 20 ] ( Table 7 ). In recent microscopy, we observed necrosis of cardiac cells, cytoplasmic vacuolization, congestion, neutrophilic myocarditis, myofibrillolysis, and pyknotic nuclei in amoxicillin-treated rabbits, while in a previous study, no authentic and related research data are available on heart pathology in connection to our study ( Table 7 ).…”
Section: Discussionmentioning
confidence: 99%